Parents' experiences of professionals' involvement for children with extreme demand avoidance. (1st January 2018) - Gore Langton, Emma; Frederickson, Norah
Abstract : Objectives: Pathological demand avoidance (PDA) is characterized by an extreme difficulty in tolerating everyday demands, with a range of 'socially manipulative' strategies used to avoid demands. Children also display poor social identity, impulsivity, and obsessive behavior. While research and knowledge about PDA is slowly growing, families continue to encounter considerable difficulties in ensuring their children's needs are understood and met by health and education services. This study explored what parents of children with extreme demand avoidance valued about professionals' input. Methods: Parents of 42 children who scored above the cut-off on a standardized measure with validated sensitivity and specificity for PDA responded to questionnaire items asking them to identify professionals' involvement and helpfulness. They were also asked what had characterized the most helpful professional involvement. Thematic analysis was used to identify the key themes in parents' responses. Results: Families tended to have high levels of professional involvement. Most professionals were experienced as helpful by the majority of parents. Three main themes were identified as characterizing helpful involvement: enabling access to services and resources, concrete outcomes such assessments and management strategies, and professional-level factors such as skills and qualities. Conclusions: Parents felt positive about practitioners who had listened to their experiences, made efforts to understand the child, and provided or arranged for help. Parents found involvement most helpful when it resulted in comprehensive assessment, appropriate intervention, practical advice and management strategies, and a focus on the well-being of all family members. The overall ratings of helpfulness are encouraging, and the specific feedback about what is most helpful could be of value in shaping services.